Photonic silver iodide nanostructures for optical biosensors - Humaira Aslam; Nazia Nusrat; Manel Mansour; Ali Umar; Aman Ullah; Shehla Honey; Muhammad Jehanzeb Sohail; Mustansar Abbas; Muhammad Waseem Aslam; Misbah Ullah Khan (Exploration of BioMat-X)
Silver iodide (AgI) nanostructures have been considered as promising candidates for optical biosensors owing to their optical characteristics of optical properties, including tunable surface plasmon resonance (SPR) and fluorescence enhancement. Such properties let one analyze biomolecules with high sensitivity, which makes them ultra-useful in diagnostics. The formed AgI nanostructures can be synthesized using chemical precipitation and template methods that enable fine-tuning of the morphology and crystallinity of the final nanostructure. The presence of SPR enhances optical signals potentially, and fluorescence enhancement helps visualize biomolecule interactions easier as the analyte concentration is usually low. Such uses of biosensors include applications in proteins, nucleic acids, and other biomolecules for progress in disease diagnosis and pharmacogenomics. Moreover, the good biocompatibility level of the created AgI nanostructures makes it possible to integrate them into biological systems safely, increasing their usage in medicine. This integration of their appealing optics, biosensing operating principles, and biocompatibility establishes their centrality in the creation of future photonic biosensors for faster, intuitive, and painless detection.